2004
DOI: 10.4314/eamj.v80i2.8650
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diarrhoeal diseases: a community based study in urban south western Ethiopia

Abstract: Objectives: To identify the determinants and describe the extent of diarrhoeal diseases among under-five children in urban Ethiopia. Design: Community based, cross-sectional study. Setting: Jimma, a town in south western Ethiopia, is an urban area with multi-ethnic population. The town is divided into 20 kebelles. Each kebelle has a population of about 5000 people Subjects: Six hundred and five children under the age of five years were selected by random sampling. There were 142 children with diarrhoeal diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
4
18
1
Order By: Relevance
“…Similar study conducted in Jimma, South west Ethiopia, revealed typhus fever preponderance among male patients (Mekasha and Tesfahun, 2004). In the current study, epidemic typhus was more prevalent among patients within the age group 41 to 50 years.…”
Section: Discussionmentioning
confidence: 96%
“…Similar study conducted in Jimma, South west Ethiopia, revealed typhus fever preponderance among male patients (Mekasha and Tesfahun, 2004). In the current study, epidemic typhus was more prevalent among patients within the age group 41 to 50 years.…”
Section: Discussionmentioning
confidence: 96%
“…Even though indicators of handwashing are commonly strongly associated with measures of socioeconomic status, 15,23,47-49 some studies have not been able to confirm this association 16 or to link socioeconomic status to lower diarrhea prevalence. 45,50 As Ram and others 51 suggested, compared with poor households, wealthier households may be able to purchase soap more regularly and may be able to prioritize the use of soap for handwashing as opposed to other purposes. In the present sample, we could not find a stronger relationship between the amount money spent on soap and handwashing frequency when respondents had a higher score on the household wealth index as opposed to when this score was low.…”
Section: Discussionmentioning
confidence: 99%
“…A multipronged approach is indicated to contain diarrheal illness in this setting and similar settings 30. Primary caregivers are aware of the existence of the disease.…”
Section: Discussionmentioning
confidence: 99%